The puzzling regulation of the interferon signaling system by the p53 tumor suppressor protein - Agnieszka Będzińska; Barbara Łasut-Szyszka; Małgorzata Krześniak; Agnieszka Gdowicz-Kłosok; Marek Rusin (Cellular and Molecular Life Sciences)
Abstract The p53 tumor suppressor exhibits antiviral activity. The viral replication is also inhibited by interferons (IFNs), cytokines that regulate immune genes via STAT transcription factors. The best studied interferons belong to the type I (e.g., IFNα1) and type II (IFNγ) groups. IFNα1 and IFNγ induce the phosphorylation of STAT1 at Tyr701. Previously, we reported that p53 activates SOCS1, a negative regulator of STAT1 phosphorylation. Based on this, we hypothesized that p53, by activating SOCS1, reduces the phosphorylation of STAT1 and attenuates the activation of genes stimulated either by IFNα1 or IFNγ. To test this hypothesis, we exposed p53-proficient and p53-deficient cells to p53 activators along with either IFNα1 or IFNγ. We then assessed STAT1 phosphorylation and the expression of interferon-regulated genes. Strong p53 activation reduced the STAT1 phosphorylation at Tyr701; however, it did not decrease the expression of most of the tested interferon-stimulated genes. On the contrary, IFNγ synergized with p53 to enhance CASP1, IFIT1 and IFIT3 expression. We conclude that the interactions between p53 and interferon-activated pathways are more complicated than initially expected, and their cooperation deserves further investigation. Moreover, we found that SOCS1 can be either up- or down-regulated by p53 depending on cell type and stress conditions.